Systematic review of the effectiveness of selected drugs for preventive chemotherapy for Taenia solium taeniasis. - Michelle M Haby; Leopoldo A Sosa Leon; Ana Luciañez; Ruben Santiago Nicholls; Ludovic Reveiz; Meritxell Donadeu (Public Library of Science (PLoS), 2020)
Background Preventive chemotherapy is a useful tool for the control of Taenia solium taeniasis and cysticercosis. The aim of this systematic review is to assess the scientific evidence concerning the effectiveness and safety of different drugs in preventive chemotherapy for T. solium taeniasis in endemic populations. Methods A systematic review was conducted of controlled and uncontrolled studies, assessing the efficacy and adverse effects (among other outcomes) of albendazole, niclosamide and/or praziquantel for preventive chemotherapy of T. solium taeniasis. A comprehensive search was conducted for published and unpublished studies. Two reviewers screened articles, completed the data extraction and assessment of risk of bias. A meta-analysis of cure rate and relative reduction in prevalence was performed. The protocol for this review was registered on the International prospective register of systematic reviews (PROSPERO), number CRD42018112533. Results We identified 3555 records, of which we included 20 primary studies reported across 33 articles. Meta-analyses of drug and dose showed that a single dose of praziquantel 10mg/kg, albendazole 400mg per day for three consecutive days, or niclosamide 2g, resulted in better cure rates for T. solium taeniasis (99.5%, 96.4% and 84.3%, respectively) than praziquantel 5mg/kg or single dose albendazole 400mg (89.0% and 52.0%, respectively). These findings have a low certainty of evidence due to high risk of bias in individual studies and heterogeneity in combined estimates. In relation to side-effects, most studies reported either no or only mild and transient side-effects within the first three days following drug administration for all drugs and doses. Conclusion Evidence indicated that praziquantel 10mg/kg, niclosamide 2g, and triple dose albendazole 400mg were effective as taenicides and could be considered for use in mass drug administration programs for the control of T. solium taeniasis. Evidence was not found that any of these drugs caused severe side effects at the indicated doses, although the extent of the available evidence was limited.